Dynamics of Criminal Law Enforcement in Drug Cases Among Adolescents: A Qualitative Study in Major Cities in Indonesia - Firayani Firayani (Journal of Strafvordering Indonesian, 2024)
This study explores the dynamics of criminal law enforcement in drug cases involving adolescents in a large city in Indonesia, using a qualitative approach. The main focus of this study is to analyze how law enforcement policies and practices are applied to drug cases among adolescents and the challenges faced in the process. Through in-depth interviews with law enforcement officers, lawyers, and social workers, as well as focus group discussions (FGDs) with adolescents and community members, this study identifies several key issues. Findings indicate that while existing criminal law policies provide strict sanctions, law enforcement is often hampered by limited resources, lack of specialized training, and an overly punitive approach to adolescents. The study also notes shortcomings in the rehabilitation services available to adolescents involved in drugs. Based on these findings, the study recommends the need for policy reform with a focus on rehabilitative approaches and improving the quality and accessibility of rehabilitation services for adolescents